2002
DOI: 10.2188/jea.12.191
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Coffee and Green Tea Consumption and All-cause Mortality in a Cohort of a Rural Japanese Population.

Abstract: We conducted a cohort study to investigate the effects of coffee and green tea consumption on all-cause mortality in a rural Japanese population. Data were obtained from 2,855 men and women aged 40-79 years in 1989, and during the subsequent 9.9 years of follow-up. Using the Cox regression model to adjust for potential confounding factors, we calculated the multivariate hazard ratios of death from all causes separately for men and women. The multivariate hazard ratio of mortality for men who consumed two or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 34 publications
(46 reference statements)
1
51
1
1
Order By: Relevance
“…In another cohort which included older individuals (40-79 years), Japanese men who consumed 2+ cups/day of coffee had a lower mortality risk (RR=0.43) compared with those who consumed less than ½ cup/ day; for those who consumed ½-1 cup/day risk was 0.70 [Iwai 2002]. No statistically significant effect was seen in women.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In another cohort which included older individuals (40-79 years), Japanese men who consumed 2+ cups/day of coffee had a lower mortality risk (RR=0.43) compared with those who consumed less than ½ cup/ day; for those who consumed ½-1 cup/day risk was 0.70 [Iwai 2002]. No statistically significant effect was seen in women.…”
Section: Discussionmentioning
confidence: 94%
“…However, exclusion of the first five years of follow-up did not appreciably change the mortality and caffeine association. In two studies [Murray 1981,Jacobsen 1986 and in women in a third [Iwai 2002], the increased mortality among those with no or low coffee consumption was limited to the first few years of follow-up. A study of potential confounders contributing to the reported associations of caffeine with disease found that of 32 risk factors only sex and cigarette smoking were important confounders [Schreiber 1988b].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations